As tutelas de urgência ex officio no processo coletivo - Costa, Daniel Carnio (2013)
This thesis aims to demonstrate that it is legal and an ethical duty of the judge to act without request of the parties in order to prevent the risk of ineffectiveness of Justice, especially in the class actions, by providing urgent measures. The effectiveness of Justice is a matter of fundamental importance to the rights in postmodern society. Hence the need to analyze adequately the management by the judge of provisional and urgent measures that guarantee the effectiveness of the judicial action as well as the usefulness and appropriateness of a judicial decision, especially in the cases of collective dimensions. In this context, the present work demonstrates that this way to deal with the conduction of the case by the judge is according to constitutional principles and legal rules applicable to individual and class actions